2018
DOI: 10.3390/atmos9030108
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Outdoor Thermal Comfort Thresholds through Public Space Design: A Review

Abstract: Based on the Köppen Geiger (KG) classification system, this review article examines existing studies and projects that have endeavoured to address local outdoor thermal comfort thresholds through Public Space Design (PSD). The review is divided into two sequential stages, whereby (1) overall existing approaches to pedestrian thermal comfort thresholds are reviewed within both quantitative and qualitative spectrums; and (2) the different techniques and measures are reviewed and framed into four Measure Review F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 122 publications
1
52
0
Order By: Relevance
“…Considering these thresholds, and as reinforced by numerous recent studies [7,23,24,25], the human thermo-physiological perception of thermal conditions exceeds that of solely T a , and conglomerates with numerous other imperative climatic variables. Within these studies, it was demonstrated that to effectively evaluate the influence of the thermal environment on individuals, it was necessary to use thermal indices centered on the energy balance of the human body [26].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Considering these thresholds, and as reinforced by numerous recent studies [7,23,24,25], the human thermo-physiological perception of thermal conditions exceeds that of solely T a , and conglomerates with numerous other imperative climatic variables. Within these studies, it was demonstrated that to effectively evaluate the influence of the thermal environment on individuals, it was necessary to use thermal indices centered on the energy balance of the human body [26].…”
Section: Introductionmentioning
confidence: 94%
“…Nevertheless, and as identified by numerous studies [22,24,34,35], the scientific community has already recognized a weakness in the studies that examine local approaches to human thermal comfort thresholds within Mediterranean climates. Similarly, the number of studies that consider the important effects (and possible mitigation efforts) of urban heat islands (UHI) upon local thermal conditions (including for Mediterranean climates) have also grown within the international scientific community (e.g., [36,37,38,39,40,41,42,43,44,45,46]).…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, user-based consideration in GBRTs. Human factors, including the physiological, psychological, and social aspects should be taken into account in the sustainable design process (Zuo, Zhao 2014;Santos Nouri et al 2018). For further refinement, it is suggested the planning and design of urban greenery be assessed not just in terms of cooling outcome and environmental effect, but also the contribution to pedestrian comfort, place making and social provision.…”
Section: Assessment Aspects Related To Mitigating Effect Of Vegetatiomentioning
confidence: 99%
“…Population growth increases pressure to the urban environments, due to the expanding demand for living and working space, which sets great challenges to urban design and planning which is supposed to be sustainable, resilient and climate sen-sitive. The awareness of the importance of urban bioclimatic conditions in outdoor environment is ever increasing, especially within the area of urban design and planning in order to contribute to thermally comfortable urban open spaces (Santos Nouri et al, 2018). Urban open spaces largely contribute to the quality of life of the citizens in terms of physical, environmental, social and economic benefits (Lai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%